Refining the picture story exercise : towards a better understanding of hope, fear, and the achievement motive - Ramsay, Jonathan E. (2015)
Decades of research have established an important distinction between the approach related and avoidance-related manifestations of the need for achievement (nAch), termed Hope of Success (HS) and Fear of Failure (FF) respectively. However, while researchers in the field of explicit motives have placed the approach-avoidance distinction at the heart of their theories of motivated behavior, implicit motive researchers have found it difficult to adequately assess and characterize HS and FF due to methodological limitations inherent in the most widely-used method of implicit motive assessment: the picture story exercise (PSE). The present research addresses these issues by redeveloping the two central components of the PSE instrument-the picture stimuli and the associated coding system-specifically for the purposes of HS and FF assessment. Study 1 sought to develop a picture set that improved both the validity and reliability of HS/FF assessment while also investigating the impact of a previously unstudied methodological consideration termed set ambiguity. Study 2 sought to consolidate existing content coding systems for PSE assessment of nAch, HS, and FF into a single composite system that simplified administration while retaining the best features of its constituents. Study 2 also clarified the relationships between nAch, HS, and FF as measured by contemporary PSE measures, establishing the equivalence of nAch and HS while reinforcing the distinction between nAch!HS and FF. In study lA, four rounds of pretesting identified eight contemporary images that were effective in arousing both HS and FF. In study lB, the validity and reliability of two versions of this picture set, one which depicted only achievement-related activity and one which was more ambiguous in its motivational content, were compared to those of a comparison picture set comprising frequently used images. The ambiguous version of the new picture set was found to exhibit better test-retest reliability than the unambiguous version, while HS and FF scores derived from the ambiguous version were found to be more predictive of theoretically relevant behaviors than scores derived from either the unambiguous version or the comparison picture set. In study 2A, data gathered during study 1 were coded for nAch, HS, and FF using the four most prevalent content coding systems. The resulting subcategory and motive scores were cluster analyzed, yielding a two factor structure that supported the HS-FF distinction while confirming the operational equivalence of nAch and HS. This clustering solution was subsequently used to guide to the construction of a simplified, consolidated content coding system in study 2B. In study 2C, data collected during study 1 were recorded using the new consolidated system. nAch/HS and FF scores derived from this new system were found to exhibit test-retest reliability, convergent validity, and predictive validity. Together, the new picture set and consolidated coding system address many of the most significant methodological issues in PSE assessment, and provide a powerful new tool for researchers wishing to investigate the approach- and avoidance-related manifestations of the achievement motive.